Titanium nitride promoted Ni-based SBA-15 catalyst for dry reforming of methane. (15th November 2018) - Chotirach, Maslin; Tungasmita, Sukkaneste; Nuntasri Tungasmita, Duangamol; Tantayanon, Supawan
Abstract: Titanium nitride (TiN) promoted nickel catalysts were synthesized and employed as an alternative catalyst in dry reforming of methane (DRM). The series of this catalyst containing various amount of Ni and TiN was prepared in two steps, direct synthesis of SBA-15 in the presence of TiN and the impregnation of Ni. The influence of Ni and TiN loading on DRM reaction was investigated using a feed ratio of CH4 /CO2 = 1, at 700 °C and atmospheric pressure for a duration of 4 h. The promising catalysts, that gave the highest feed conversions and product yields, were selected for further investigation, compared to non-promoted Ni catalyst using the same conditions but for 12 h of reaction. The results showed that the performance of Ni catalyst was improved by the incorporation of TiN. The modified catalysts provided not only high catalytic activity but also enhancement of coke resistance. Highlights: TiN has the potential to promote the catalytic activity of Ni catalyst supported on SBA-15 in dry reforming of methane. The presence of TiN can suppress coke deposition on Ni/SBA-15 catalyst. The medium-strength basicity was improved by the interaction between Ni and TiN. 10Ni/5TiN-SBA-15 catalyst is the most effective catalyst with the highest catalytic activity and the least carbon deposition.